THE DIMENSIONS OF INFORMATION LITERACY: privileging rights and reducing the social vulnerability - Brito, Tania Regina de [UNESP]; Vitorino, Elizete Vieira (Univ Federal Campina Grande, 2022)
This article proposes reflections about the information literacy and its dimensions, presenting an approach and connection with the studies about social vulnerability, trying to understand the multidimensionality of both. It brings, as a possibility, to privilege rights and to reduce the social vulnerability using the dimensions of information literacy and information education. It refers to a theoretical foundation part of a master research, constructed from a bibliographic study, using CAPES journal and data from Base de Dados Referenciais de Artigos de Periodicos em Ciencia da Informacao (Brapci). The selection standards established were: articles about the information literacy concept, its progress, aspects, dimensions of information literacy, relation between information literacy and mediation information and information literacy as a mediator of the democratization of information and reduction of social vulnerability. It presents a summary of the aspects of social vulnerability in the technical, aesthetic, ethical and political dimensions. It considers that the development of information literacy presents potential to reduce multiple vulnerabilities, in special, the information one. It extends, in this way, the social and professional possibilities for vulnerable people.
Keywords: Information literacy; Dimensions of information literacy; Social vulnerability; Learning throughout life